2012
DOI: 10.1007/s10815-012-9823-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of conventional IVF and ICSI on sibling oocytes in the case of isolated teratozoospermia

Abstract: Because isolated teratozoospermia did not influence the major indices of IVF and the unnecessary use of ICSI is time-consuming, costly and potential risks, couples with isolated teratozoospermia need not be subjected to ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
4
18
0
Order By: Relevance
“…Conversely, according to Lockwood et al [16], teratozoospermia is not a parameter to be taken into account for the choice of ART technique and allows even intra-uterine inseminations. These results confirm those reported by Fan et al [17]. Many other groups also previously demonstrated the absence of effect of isolated teratozoospermia on IVF results [1821].…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, according to Lockwood et al [16], teratozoospermia is not a parameter to be taken into account for the choice of ART technique and allows even intra-uterine inseminations. These results confirm those reported by Fan et al [17]. Many other groups also previously demonstrated the absence of effect of isolated teratozoospermia on IVF results [1821].…”
Section: Discussionsupporting
confidence: 92%
“…Oocytes randomized to the ICSI group in some studies remained in the "ICSI group" regardless of the ability to perform ICSI [11,21,31]. Other studies included only randomized oocytes that qualified to undergo ICSI to be included in the analysis [19,32].…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1996, Yang et al published the first results of randomly assigned sibling oocytes to either ICSI or CF and demonstrated that similar rates of fertilization and pregnancy occurred in the sample of 13 couples with a total of 280 oocytes [17]. Additional studies have analyzed this approach in patients with a variety of diagnoses and have demonstrated mixed results regarding fertilization, total fertilization failure, morula development, implantation and clinical pregnancy [11,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The most consistent finding from prior studies is a decrease in the total fertilization failure per IVF cycle in the ICSI groups [11,21].…”
Section: Introductionmentioning
confidence: 99%
“…Another study compared the results after randomization between IVF or ICSI on sibling oocytes in a group of patients with isolated teratozoospermia (<4% strict criteria) ( n = 183) and a group of patients with all normal sperm parameters ( n = 258). They found no significant difference in fertilization rates, day 3 embryonic morphology, pregnancy and spontaneous abortion rates between the groups in either IVF or ICSI (Fan et al ., ).…”
Section: Prognostic Value Of Sperm Morphology Assessment Before Artmentioning
confidence: 97%